Delaying the Occurrence of Bar Buckling in RC Columns Confined with SRG Jacketing - Georgia E. Thermou; Sousana Tastani (Applied Sciences, 2023)
This paper investigates experimentally the structural performance of substandard reinforced concrete (RC) short columns confined with steel-reinforced grout (SRG) jackets under monotonically increasing uniaxial compression. The study comprised 24 square cross section short RC columns having alternative arrangements of shear reinforcement (ratio of stirrup spacing to longitudinal bar diameter ranging from 4.2 to 12.5). The short columns were retrofitted with externally applied SRG jacketing differing by the density of the fabric (4 cords/in and 12 cords/in) and the number of fabric layers (1 and 2). The test results showed that retrofitting significantly changed the behaviour of the specimens compared to the unconfined counterparts. For columns at risk of premature failure due to insufficient support of compression bars provided by the sparse stirrups, the SRG jackets delayed bar buckling, enabling the members to achieve greater strength and deformation capacity. The well-detailed specimens helped establish the maximum effectiveness of SRG confinement.